FIGUR PEREMPUAN JAWA DALAM DAMAR KURUNG SEBAGAI INSPIRASI MOTIF BATIK KHAS GRESIK - Aniendya Christianna; Luri Renaningtyas (Dinamika Kerajinan dan Batik: Majalah Ilmiah, 2021)
Javanese women have a position as a pillar of Javanese culture, not only physically but also psychologically which includes perceptions, imaginations, and interpretations of Javanese cultural values. Damar Kurung is a lantern from the 16th century that serves as a marker of the coming of the Month of Ramadan. This culture of light has been gradually eroded by its irrelevant function, especially since electric lights dominate human life. The decoration that decorated the Damar Kurung has been preserved for generations by a female artist: Masmundari. Masmundari died at the age of more than 100 years ago in 2005, after the death of Damar Kurung also faded. This research is qualitative research using a descriptive method that is used to describe the performance of Javanese women in the Damar Kurung decoration. This research was carried out for approximately 8 months which included the research phase, the design phase and the implementation phase of the design results. The data analysis method used is descriptive, which is useful for describing the factual findings of the characteristics of the Damar Kurung ornamental variety along with its historical chronology. The data findings are classified according to the findings of the female performance themes and then developed as an innovation in the typical Gresik batik motif. The purpose of this research is the development of Damar Kurung decoration into batik motifs is one of the conservation efforts to preserve Damar Kurung as a national intangible heritage. And to find out the identity and role of women's gender in Javanese culture. The output of this research is also expected to contribute to the designers and practitioners of the art and/or crafts in order to be able to utilize the local cultural heritage to improve the economy of the creative industries